Perak i-care mobile application / Nor Muhammad Irfan Hakimi Hashim ... [et al.] - Hakimi Hashim, Nor Muhammad Irfan; Sheikh Nehmil Emir, Sheikh Muhammad Adam Iskandar; Jumahan, Muhammad Fareez Ridzuan; Hairudin, Nur Hakimah; Mohammad Rafi, Nureen Nazifah (2024)
This mobile application lists all health service providers in Perak including pharmacy, medical facilities, hospitals, private maternity clinics, public and private veterinary clinics. In addition, this application suggests the best solutions for the issues described by the consumers. The objective is to make it easy to locate public or private amenities by informing locations and offering details like reviews and comments from previous customers. A user needs to enter their name and the district they live in on the application. The user will have the choice of selecting from a variety of public or private service facilities, including hospitals, pharmacies, clinics, and animal clinics. Then, the user will see a selection of service facilities, evaluation, feedback, and directions to the location of their choice. The consumers will be satisfied because the options provided are useful.